Decision Support System Best Cage Selection for Chicken Raising - Pandika Andio Efendi; Riki Riki; Hartana Wijaya; Indah Fenriana (bit-Tech, 2021)
Chicken farming is considered not to require the application of an information system, however, the application of a decision-making system can increase the chances of getting bigger profits. In one time raising chickens requires large capital and the right time when planning sales. Therefore, the selection of decisions is an important factor in an ongoing business. Companies often experience losses which, although not too large, but also occur sustainably will affect the company's finances. It is hoped that the chicken rearing decision support system can also assist in managing the data that comes into the company. Decision support systems will be used in business to help meet company targets and reduce risk. Electre stands for Elimination and Choice Translating Reality which is a method of determining the ranking order through pairwise comparisons between alternatives and the appropriate criteria. Standardization and the use of complete data in decision making can increase the percentage of profit and satisfaction which increases partner integrity